Bi-directional electric vehicle fast charging station with novel reactive power compensation for voltage regulation - Yong J.Y.; Ramachandaramurthy V.K.; Tan K.M.; Mithulananthan N. (Elsevier Ltd, 2023)
Electric vehicles; Reactive power; Topology; Voltage control; Voltage regulators; Voltage control; Bi-directional; Fast charging; Fast charging stations; Low voltage distribution network; Operational voltage; Reactive power compensation; Steady state voltage; Transportation sector; Charging (batteries); Electric vehicles